Identification of a novel autoantigen eukaryotic initiation factor 3 associated with polymyositis - Betteridge, Zoe; Chinoy, Hector; Vencovsky, Jiri; Winer, John; Putchakayala, Kiran; Ho, Pauline; Lundberg, Ingrid; Danko, Katalin; Cooper, Robert; McHugh, Neil (Rheumatology, 2020)
OBJECTIVES: To describe the prevalence and clinical associations of autoantibodies to a novel autoantigen, eukaryotic initiation factor 3 (eIF3), detected in idiopathic inflammatory myositis. METHODS: Sera or plasma from 678 PM patients were analysed for autoantigen specificity by radio-labelled protein immunoprecipitation (IPP). Samples immunoprecipitating the same novel autoantigens were further analysed by indirect immunofluorescence and IPP using pre-depleted cell extracts. The autoantigen was identified through a combination of IPP and MALDI-TOF mass spectrometry, and confirmed using commercial antibodies and IPP-western blots. Additional samples from patients with DM (668), DM-overlap (80), PM-overlap (191), systemic sclerosis (150), systemic lupus erythematosus (200), Sjogren's syndrome (40), rheumatoid arthritis (50) and healthy controls (150) were serotyped by IPP as disease or healthy controls. RESULTS: IPP revealed a novel pattern in three PM patients (0.44%) that was not found in disease-specific or healthy control sera. Indirect immunofluorescence demonstrated a fine cytoplasmic speckled pattern for all positive patients. Mass spectrometry analysis of the protein complex identified the target autoantigen as eIF3, a cytoplasmic complex with a role in the initiation of translation. Findings were confirmed by IPP-Western blotting. The three anti-eIF3-positive patients had no history of malignancy or interstitial lung disease, and had a favourable response to treatment. CONCLUSION: We report a novel autoantibody in 0.44% of PM patients directed against a cytoplasmic complex of proteins identified as eIF3. Although our findings need further confirmation, anti-eIF3 appears to correlate with a good prognosis and a favourable response to treatment.
Keywords: dospělí; systémový lupus erythematodes; Female; Immunoprecipitation; biologické markery; Rheumatic Fever; Blotting, Western; Biomarkers; Adult; ženské pohlaví; eukaryotický iniciační faktor 3; lidé; imunoprecipitace; Immunosuppressive Agents; Sensitivity and Specificity; studie případů a kontrol; revmatická horečka; senzitivita a specificita; referenční hodnoty; stupeň závažnosti nemoci; hmotnostní spektrometrie; Lupus Erythematosus, Systemic; Sjögrenův syndrom; Humans; Middle Aged; western blotting; retrospektivní studie; Male; progrese nemoci; Case-Control Studies; polymyozitida; Autoantibodies; Polymyositis; Reference Values; Disease Progression; autoantigeny; Mass Spectrometry; Eukaryotic Initiation Factor-3; lidé středního věku; mužské pohlaví; Severity of Illness Index; Autoantigens; Retrospective Studies; imunosupresiva; Sjogren's Syndrome; autoprotilátky